A new species of Syzygium (Myrtaceae) from the southern Western Ghats of Kerala, India - Shareef, S. M.; Kumar, E. S.santhosh; Shaju, T. (Phytotaxa, 2012)
A new species of Syzygium, S. palodense is described and illustrated from the southern Western Ghats, Kerala, India. It is similar to S. densiflorum and S. rubicundum but differs from both by the slightly winged branchlets, subopposite or alternate leaves with obliquely cuneate bases, thick and robust petioles, creamy-white flowers with campanulate calices and subglobose to obovoid fruits.